(untitled) (Communications in Mathematical Research, 2022)
We prove the Hölder continuity of a harmonic map from a domain of a sub-Riemannian manifold into a locally compact manifold with nonpositive curvature, and more generally into a non-positively curved metric space in the Alexandrov sense.